Fikih Hak Asasi Manusia (Analisis Piagam PBB dalam Perspektif Hukum Pidana Islam) - Miftahul ulum (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2017)
Human rights issues are still a never-ending debate, between a Western perspective and an Islamic perspective. Muslims responded in various ways. The difference of views on the articles in the declaration is inseparable from the differences in the background and interpretation of religious and historical texts in the golden age of Islamic history. Among the attitudes of Islamists to the Declaration of Human Rights, as follows: First, reject the Declaration of Human Rights. There are several classical reasons which are the factors behind why Islamists reject them. Among other things, it is a very different socio-cultural condition between the West and Islam. References of different values, in the West embrace liberal values ​​or abandon the values ​​of Christianity, which assume authority entirely in the hands of man, without including the sovereignty of God. The paradigm of some Muslims to this day, still assume that religion has universal coverage, while human rights have only part of the universal religion rather than vice versa. Secondly, to receive fully, for seeing the teachings and values ​​of Islam in a substance. The group is of the opinion that the Declaration of Human Rights is in accordance with the teachings of Islam, both in substance and mission that fought. The principles in the Declaration of the United Nations on Human Rights have been in line with the principles of Islamic jurisprudence (kulliyat al-khams: hifdh al-din, the right to upholding religion and freedom of religion, al-'aql: the right to the development of sound thinking, including the right to freedom of thought and opinion, al-nafs, the protection of the right to life, al-nasl, the assurance of the right to the development of kind and descent, al-mal, the protection of the right to property ownership).